Durability aspects in self-compacting siderurgical aggregate concrete. (July 2021) - Sosa, I.; Tamayo, P.; Sainz-Aja, J.A.; Thomas, C.; Setién, J.; Polanco, J.A.
Abstract: The steel industry generated approximately 18 Mt of electric arc furnace slags in 2016. It is estimated that construction generates 10% of man-made CO2 emissions. To mitigate these two problems, the valorisation of these slags by using them to manufacture siderurgical concrete is considered. As there is a large volume of these aggregates, which have good mechanical properties, it seems sensible to propose their valorisation, even though this implies a series of modifications in concrete properties such as better mechanical properties or higher density. These modifications in the concrete properties make it especially suitable for some concrete applications, such as its use in marine gravity structures, e.g. dams, breakwaters or Gravity-Based Foundation (GBF). In this research, the suitability of these siderurgical concretes for exposure to marine environments has been proved in laboratory and by keeping some reinforced concrete samples in a tidal race for 10 months. Special samples were made in order to analyse the chlorine penetration; truncated conical shaped test pieces were used to analyse the effect of different coating thicknesses on the protection of the reinforcement. After the concrete characterization, it was found that the designed concretes had an adequate durability for exposure to the marine environment. Highlights: A self-compacting concrete using siderurgical aggregate has been achieved. Siderurgical self-compacting requires special mixing considerations. The shape and characteristics of the aggregates influence the floability The iron and steel self-compacting concrete is a concrete with high mechanical performance. The iron and steel self-compacting concrete is a concrete with a great durability against aggressive agents.